1997
DOI: 10.1084/jem.185.4.663
|View full text |Cite
|
Sign up to set email alerts
|

IgE Enhances Mouse Mast Cell FcεRI Expression In Vitro and In Vivo: Evidence for a Novel Amplification Mechanism in IgE-dependent Reactions

Abstract: The binding of immunoglobulin E (IgE) to high affinity IgE receptors (FcεRI) expressed on the surface of mast cells primes these cells to secrete, upon subsequent exposure to specific antigen, a panel of proinflammatory mediators, which includes cytokines that can also have immunoregulatory activities. This IgE- and antigen-specific mast cell activation and mediator production is thought to be critical to the pathogenesis of allergic disorders, such as anaphylaxis and asthma, and also contributes to host defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
292
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(322 citation statements)
references
References 42 publications
21
292
2
3
Order By: Relevance
“…Eosinophils were then analyzed by flow cytometry. Cells kept in culture for 4 days without IgE almost completely lost Fc⑀RI expression, as observed for mouse mast cells (45) (Fig. 5a), whereas in the presence of IgE, about 50% of the eosinophil population was expressing Fc⑀RI, albeit at a lower level than freshly isolated cells (Fig.…”
Section: Fc⑀ri Expression On Eosinophils Is Up-regulated By Ige In Vitromentioning
confidence: 81%
See 1 more Smart Citation
“…Eosinophils were then analyzed by flow cytometry. Cells kept in culture for 4 days without IgE almost completely lost Fc⑀RI expression, as observed for mouse mast cells (45) (Fig. 5a), whereas in the presence of IgE, about 50% of the eosinophil population was expressing Fc⑀RI, albeit at a lower level than freshly isolated cells (Fig.…”
Section: Fc⑀ri Expression On Eosinophils Is Up-regulated By Ige In Vitromentioning
confidence: 81%
“…As described for mouse mast cells (42,45) and basophils (43) as well as for rat mast cells (44), receptor expression was up-regulated on eosinophils by incubation with its ligand. A very strong adherence of macrophages to culture wells during the 4-day incubation prevented us from assessing the phenomenon in this cell type.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fc⑀RI expression could be up-regulated up to 32-fold by in vitro incubation of mast cells with IgE or by injection of IgE in vivo (14,15). Therefore, IgE-mediated Fc⑀RI up-regulation is not an artifact observed in cultured cell lines.…”
Section: Drastic Up-regulation Of Fc⑀ri On Mast Cells Is Induced By Imentioning
confidence: 89%
“…It was recently reported that levels of Fc⑀RI expression on mast cells freshly isolated from IgE-deficient mice were extremely low (20% of normal level) (14). However, Fc⑀RI expression could be up-regulated up to 32-fold by in vitro incubation of mast cells with IgE or by injection of IgE in vivo (14,15).…”
Section: Drastic Up-regulation Of Fc⑀ri On Mast Cells Is Induced By Imentioning
confidence: 99%
“…Because cell-surface FceRI expression is a critical element in the FceRI-dependent mast cell response [10], we examined the mechanism for down-regulation of FceRI by 25-OHC. As shown in Fig.…”
Section: -Ohc Decreases Assembly Of Fceria and Fceribc In Mast Cellsmentioning
confidence: 99%